Direct and Indirect Effects of Injunctive Norms on Marijuana Use: The Role of Reference Groups - Labrie, Joseph W. (Rutgers University, 2010)
OBJECTIVE: Little work has evaluated the relationship between injunctive norms and marijuana use. This study sought to establish whether misperceptions exist between perceived injunctive norms of typical college students and the actual approval level of the students. We also examined respondents’ perceptions of which groups (typical student, close friends, and parents) were the most and least approving of marijuana. These variables were then applied to an explanatory model to assess their relationships with marijuana use. METHOD: Participants were 3,753 students (61% female) randomly recruited from two West Coast campuses. Participants were asked about their own marijuana use and their own approval toward marijuana. Injunctive norms were assessed by asking respondents about their perceptions of how much other reference groups approved of marijuana. RESULTS: Students overestimated the extent to which the typical student approves of marijuana use. A path model showed that perceived approval of both close friends and parents predicted actual/self-approval, which in turn was most predictive of personal marijuana use. Perceptions of typical-student and close friends’ approval also directly predicted one's own use, whereas the path from parental approval to marijuana use was fully mediated by one's own approval. CONCLUSIONS: Findings suggest that perceived injunctive norms may function differently with respect to marijuana use than they do with respect to alcohol use and raise questions about how to incorporate social-normative information into marijuana interventions.